Visceral Adipose Tissue Inflammation and Vascular Complications in a Rat Model with Severe Dyslipidemia: Sex Differences and PAI-1 Tissue Involvement - Irena Markova; Martina Hüttl; Natalie Gayova; Denisa Miklankova; Kristyna Cerna; Martina Kavanova; Petra Skaroupkova; Sona Cacanyiova; Hana Malinska (Biomolecules)
We investigated the sex-dependent effects of inflammatory responses in visceral adipose tissue (VAT) and perivascular adipose tissue (PVAT), as well as hematological status, in relation to cardiovascular disorders associated with prediabetes. Using male and female hereditary hypertriglyceridemic (HHTg) rats—a nonobese prediabetic model featuring dyslipidemia, hepatic steatosis, and insulin resistance—we found that HHTg females exhibited more pronounced hypertriglyceridemia than males, while HHTg males had higher non-fasting glucose levels. Additionally, HHTg females had higher platelet counts, larger platelet volumes, and lower antithrombin inhibitory activity. Regarding low-grade chronic inflammation, HHTg males exhibited increased serum leptin and leukocyte levels, while females had increased serum interleukin-6 (IL-6). Both sexes had increased circulating plasminogen activator inhibitor-1 (PAI-1), higher PAI-1 gene expression in VAT and PVAT, and elevated intercellular adhesion molecule-1 (ICAM-1) gene expression in the aorta, contributing to endothelial dysfunction in the HHTg strain. However, HHTg females had lower tumor necrosis factor alpha (TNFα) gene expression in the aorta. Severe dyslipidemia in this prediabetic model was associated with hypercoagulation and low-grade chronic inflammation. The increase in PAI-1 expression in both VAT and PVAT seems to indicate a link between inflammation and vascular dysfunction. Despite the more pronounced dyslipidemia and procoagulation status in females, their milder inflammatory response may reflect an association between reduced cardiovascular damage and prediabetes.